2023
DOI: 10.1371/journal.pone.0274079
|View full text |Cite
|
Sign up to set email alerts
|

Soccer academy practitioners’ perceptions and application of bio-banding

Abstract: The primary aims of this study were to examine the application of maturity status bio-banding within professional soccer academy programmes and understand the methods employed, the intended objectives, and the potential barriers to bio-banding. Using a mixed method design, twenty-five professional soccer academy practitioners completed an online survey designed to examine their perceptions of the influence of maturation on practice, their perceptions and application of bio-banding, and the perceived barriers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Following this, to determine a binary (agree or disagree; important or not important) interpretation, data for composite component data points (i.e., strongly agree-agree, strongly disagree-disagree; very important-important, not at all important-low importance) were aggregated. In accordance with similar previous research [63][64][65], and due to the limited, non-parametric categorical data collected, statistical assumptions were violated (i.e., the Pearson's chi-squared test necessitates that for expected frequencies, cell values should be >5 in �80% of cells, and �1 in 100% of cells) [66]) and therefore unviable. Accordingly, data was reported descriptively.…”
Section: Part B: Semi Structured Interviewssupporting
confidence: 69%
“…Following this, to determine a binary (agree or disagree; important or not important) interpretation, data for composite component data points (i.e., strongly agree-agree, strongly disagree-disagree; very important-important, not at all important-low importance) were aggregated. In accordance with similar previous research [63][64][65], and due to the limited, non-parametric categorical data collected, statistical assumptions were violated (i.e., the Pearson's chi-squared test necessitates that for expected frequencies, cell values should be >5 in �80% of cells, and �1 in 100% of cells) [66]) and therefore unviable. Accordingly, data was reported descriptively.…”
Section: Part B: Semi Structured Interviewssupporting
confidence: 69%
“…These biases may result in the over-selection of early-maturing players, leading to long-term consequences for the development of late-maturing players, who often quit the sport prematurely due to a temporary physical disadvantage associated with the maturation process [2]. Grouping children by biological maturity rather than age (commonly referred to as bio-banding [1; 7; 8] commonly used with professional soccer academies [1;3; 9; 10] helps coaches assess players development [11] and help ensure that players of all maturity levels have equal opportunities to develop their skills and reach their full potential [8].…”
Section: Introductionmentioning
confidence: 99%
“…These psychological aspects are important for talent identification, as late-maturing players have been characterised as being achievement-oriented and highly skilled (between 13 and 14 years; [16]), which might be linked, in part, to the onset and cessation of peak height velocity (PHV) [17,18]. For instance, our previous findings have shown that performing in maturity mis-matched (i.e., late maturing versus early maturing) categorised groups of players (using 'bio-banding'; [19][20][21]) during small-sided games provides late-maturing players with a mis-matched environment which allows them to exhibit a number of desirable psychological characteristics [22]. This maturity-related performance phenomena can be in part explained by the 'underdog hypothesis' [15,23], which proposes that late-maturing players may have established enhanced psychological skills that permit them to compete with their more mature team mates on equal terms [23].…”
Section: Introductionmentioning
confidence: 99%